NTRC Effects on Non-Photochemical Quenching Depends on PGR5 - Belen Naranjo; Jan-Ferdinand Penzler; Thilo Rühle; Dario Leister (MDPI AG, 2021)
Non-photochemical quenching (NPQ) protects plants from the detrimental effects of excess light. NPQ is rapidly induced by the trans-thylakoid proton gradient during photosynthesis, which in turn requires PGR5/PGRL1-dependent cyclic electron flow (CEF). Thus, Arabidopsis thaliana plants lacking either protein cannot induce transient NPQ and die under fluctuating light conditions. Conversely, the NADPH-dependent thioredoxin reductase C (NTRC) is required for efficient energy utilization and plant growth, and in its absence, transient and steady-state NPQ is drastically increased. How NTRC influences NPQ and functionally interacts with CEF is unclear. Therefore, we generated the A. thaliana line pgr5 ntrc, and found that the inactivation of PGR5 suppresses the high transient and steady-state NPQ and impaired growth phenotypes observed in the ntrc mutant under short-day conditions. This implies that NTRC negatively influences PGR5 activity and, accordingly, the lack of NTRC is associated with decreased levels of PGR5, possibly pointing to a mechanism to restrict upregulation of PGR5 activity in the absence of NTRC. When exposed to high light intensities, pgr5 ntrc plants display extremely impaired photosynthesis and growth, indicating additive effects of lack of both proteins. Taken together, these findings suggest that the interplay between NTRC and PGR5 is relevant for photoprotection and that NTRC might regulate PGR5 activity.